2020
DOI: 10.4149/neo_2019_190217n135
|View full text |Cite
|
Sign up to set email alerts
|

HMGA1-mediated miR-671-5p targets APC to promote metastasis of clear cell renal cell carcinoma through Wnt signaling

Abstract: This study aimed to investigate the effect of miR-671-5p on metastasis of clear cell renal cell carcinoma (ccRCC) and underlying mechanism involved. The migration and invasion of ccRCC cells were determined by transwell and boyden assays in vitro and in vivo. Genes mRNA and protein expression were detected by quantitative polymerase chain reaction (qPCR) and western blot analysis, respectively. The target gene of miRNA was confirmed by luciferase reporter assays. Transcriptional regulation of miRNA by transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
(21 reference statements)
1
17
0
Order By: Relevance
“…For example, Tan et al ( 9 , 10 ) have demonstrated that miR-671-5p suppresses forkhead box M1-mediated epithelial-to-mesenchymal transition (EMT) during the oncogenesis of breast cancer. Similarly, miR-671-5p exerts suppressive effects on the cell proliferation in esophageal squamous cell carcinoma ( 11 ), osteosarcoma ( 12 ) and clear cell renal cell carcinoma ( 13 ). By contrast, miR-671-5p targets cerebellar degeneration-related autoantigen 1 to promote the proliferation, migration and invasion of glioblastoma cells ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tan et al ( 9 , 10 ) have demonstrated that miR-671-5p suppresses forkhead box M1-mediated epithelial-to-mesenchymal transition (EMT) during the oncogenesis of breast cancer. Similarly, miR-671-5p exerts suppressive effects on the cell proliferation in esophageal squamous cell carcinoma ( 11 ), osteosarcoma ( 12 ) and clear cell renal cell carcinoma ( 13 ). By contrast, miR-671-5p targets cerebellar degeneration-related autoantigen 1 to promote the proliferation, migration and invasion of glioblastoma cells ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…In these tumors, miR-671 was demonstrated to show inhibit the malignant phenotypes of tumor cells by targeting SOX6, CCND2, and FOXM1 (23)(24)(25)(26)(27). However, miR-671 may function as an oncogenic miRNA in other types of cancer (28,29). In our study, miR-671 was identified as a downstream effector of circ_0092314 in PAAD cells, in which the tumor-promoting effects of c i r c _ 0 0 9 2 3 1 4 c o u l d b e bl o c k e d t h r o u g h mi R -6 7 1 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…HMGA1 was a well‐studied transcription factor that involves in cell metastasis and EMT in RCC. Recently, Chi et al (2020) have reported the oncogene HMGA1 transcriptionally enhanced miR‐671‐5p expression to form HMGA1/miR‐671‐5p/APC signaling, thus inducing the EMT process in RCC. Similarly, Dong et al (2020) have also reported the EMT‐regulatory role of HMGA1 in RCC.…”
Section: Discussionmentioning
confidence: 99%